Exploring Quasiparticle Excitation in a Multireference Many-Body Framework - Kronkvist,Erik (2025)
This thesis extends the novel model of reference [1] to enable the description of odd-even and odd-odd nuclei, as well as negative-parity states of even-even nuclei. The method employs quasi-particle blockings of Hartree-Fock-Bogoliubov states to represent states with an odd number of particles using states with an even number of particles. The Bloch–Messiah decomposition for odd nucleon states is implemented, and effective symmetry restoration is achieved through the use of projection operators. Furthermore, this work introduces multi-quasi-particle excitations based on wavefunctions with an odd number of particles to better capture collective and non-collective behaviours of the nuclei. The implementations are performed to create a unified model, able to handle both even and odd mass nuclei. The implemented model is applied to the neighbouring isotopes of 24Mg, as well as the negative parity spectra of 24Mg for the first time. The model is further used to predict the positive and negative parity spectra of 33Mg. These calculations demonstrate the model’s capability to describe nuclear systems beyond the even–even case, offering a unified model to describe structural properties of nuclei across the nuclear chart.
Keywords: Nuclear physics